PBP4 Mediates β-Lactam Resistance by Altered Function - Chatterjee, Som S. (Antimicrob Agents Chemother, 2017)
Penicillin binding protein 4 (PBP4) can provide high-level β-lactam resistance in Staphylococcus aureus. A series of missense and promoter mutations associated with pbp4 were detected in strains that displayed high-level resistance. We show here that the missense mutations facilitate the β-lactam resistance mediated by PBP4 and the promoter mutations lead to overexpression of pbp4. Our results also suggest a cooperative interplay among PBPs for β-lactam resistance.